Positive lithium supplement agent, preparation method, positive pole piece and secondary battery
By doping rare earth elements and transition metal elements in lithium-rich lithium ferrate and loading carbon coating on the core surface to form a modified positive lithium supplement agent, the air stability, conductivity and specific capacity of Li5FeO4 are solved. The problem has significantly improved the performance of lithium-ion batteries.
Patent Information
- Application Number
- CN202411670286.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-20
AI Technical Summary
As a positive electrode lithium supplement agent, Li5FeO4 has problems such as extremely poor air stability, poor conductivity and low actual specific capacity, which limits its industrial application in lithium-ion batteries.
By doping rare earth elements and transition metal elements in lithium-rich lithium ferrate and loading a carbon coating on the core surface, a modified positive lithium supplement agent is formed. This method improves the conductivity, air stability and specific capacity of the positive electrode lithium supplement agent through the combination of multi-element co-doping and carbon cladding.
The conductivity, air stability and specific capacity of the positive electrode lithium supplement agent are significantly improved, thereby improving the first Coulomb efficiency, energy density and cycle life of lithium-ion batteries.
Smart Images

Figure CN119481006A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of battery materials, and in particular to a positive electrode lithium supplement, a preparation method, a positive electrode plate and a secondary battery. Background Art
[0002] Lithium-ion batteries are widely used in portable electronic devices, electric vehicles and energy storage systems due to their high energy density, long cycle life and good rate performance. How to further improve the energy density and cycle life of lithium-ion batteries has also become a research hotspot in the field of lithium-ion batteries. Lithium loss is the direct cause of battery degradation. During the first charge and discharge process of the battery, part of the active lithium will react with the electrolyte at the solid-liquid interface of the negative electrode to form a solid electrolyte interface (SEI) film, and permanently consume a large amount of active lithium, thereby reducing the initial coulomb efficiency of the battery and causing the battery capacity and energy density to decay.
[0003] Lithium replenishment technology, also known as pre-lithiation technology, is to add lithium replenisher to the battery before it works to replenish lithium ions, thereby offsetting the permanent consumption of active lithium in the battery to improve the reversible energy density of the battery. Lithium replenishment technology includes negative electrode lithium replenishment and positive electrode lithium replenishment. Compared with the difficult and high-investment negative electrode lithium replenishment technology, the positive electrode lithium replenishment process is simple, low-cost and safe, and can be combined with traditional battery production processes, with broad industrial application prospects.
[0004] Lithium iron oxide (Li5FeO4) has a theoretical specific capacity of 864mAh / g. Its stable lithium-transition metal oxide structure can replace metallic lithium to make up for the active lithium in the positive electrode consumed by the formation of SEI film in lithium-ion batteries. Using Li5FeO4 as a positive electrode lithium supplement can significantly improve the first coulombic efficiency, energy density and cycle life of lithium-ion batteries in systems such as lithium iron phosphate, lithium iron manganese phosphate, and NCM ternary. However, Li5FeO4 has extremely poor air stability, poor conductivity and low actual specific capacity, which seriously limits its industrial application. Summary of the invention
[0005] In view of the technical problems existing in the background technology, the present application provides a positive electrode lithium supplement, a preparation method, a positive electrode plate and a secondary battery, aiming to solve the problems of Li5FeO4 such as extremely poor air stability, poor conductivity and low actual specific capacity.
[0006] In the first aspect, the present invention provides a positive electrode lithium supplement, including a core and a carbon coating layer covering the core; the core includes modified lithium-rich lithium ferrite, and the expression is: Li5Fe 1-x-y A x B y O4;
[0007] Among them, 0 <x≤0.03,0<y≤0.03;
[0008] The A element includes one or more of La, Sc, Y, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb and Lu;
[0009] The B element includes one or more of Co, Ni, Cu, Zn, Mn, Cr, V, Ti, Zr, Nb, Mo, Ta, W, Sn, Sb and Al;
[0010] The mass ratio of the core to the carbon coating is 100:(0.1~6).
[0011] In the technical solution of the embodiment of the present application, the core of the positive electrode lithium supplement agent adopts modified lithium-rich lithium iron oxide, and the conductivity of the positive electrode lithium supplement agent is improved by doping element A and element B in the lithium-rich lithium iron oxide at the same time, and the synergy of at least two elements is used to improve the conductivity of the positive electrode lithium supplement agent, making the migration and removal of lithium ions easier, which is manifested in a macroscopic way as a significant increase in the specific capacity of the positive electrode lithium supplement agent. At the same time, the carbon coating layer on the surface of the core can effectively isolate water and CO2 in the air, inhibit the occurrence of side reactions, and thus improve the air stability of the positive electrode lithium supplement agent.
[0012] Understandably, in this application, if the quality of the carbon coating layer is low, it will affect the coating uniformity of the carbon coating layer, and the protection effect on the core is not good; if the quality of the carbon coating layer is high, it will cause the electrical performance of the positive electrode lithium supplement agent to decline; by controlling the mass ratio of the core and the carbon coating layer within the range of 100: (0.1~6), it can ensure that the carbon coating layer forms a good coating effect on the surface of the core, and will not adversely affect the electrical performance of the positive electrode lithium supplement agent. Therefore, the positive electrode lithium supplement agent provided in this application has the advantages of high conductivity, good air stability and high specific capacity, which can significantly improve the first coulomb efficiency, energy density and cycle life of secondary batteries such as lithium ion batteries.
[0013] In some embodiments, the thickness of the carbon coating layer is 0.1 nm to 500 nm.
[0014] In this embodiment, the thickness of the carbon coating layer is controlled between 0.1nm and 500nm, which can be relatively evenly covered on the surface of the core, forming a good conductive network, promoting electron transfer, and improving the rate performance of the material. If the thickness of the carbon coating layer is too small, a conductive network cannot be formed, and the conductivity of the material cannot be improved; if the thickness of the carbon coating layer is too large, the overall weight of the material will increase, and the specific capacity of the material will be reduced.
[0015] In some embodiments, the D50 particle size of the core is between 1 μm and 3 μm.
[0016] In this embodiment, the D50 particle size of the core of the positive electrode lithium supplement agent is moderate, which can ensure that the diffusion path of lithium ions inside the material is not too long or too short, and lithium ions can be embedded and extracted relatively quickly, thereby improving the specific capacity and rate performance of the battery. At the same time, within this particle size range, the positive electrode lithium supplement agent is easy to disperse in the electrode slurry, which is conducive to forming a positive electrode active coating with high flatness and good uniformity, thereby improving the consistency and stability of the positive electrode.
[0017] In some embodiments, the specific capacity of the positive electrode lithium supplement is ≥680 mAh / g.
[0018] In this embodiment, the positive electrode lithium supplement has a high specific capacity and can provide a large amount of additional lithium source for the battery, thereby increasing the overall capacity of the battery and improving the rate performance, and maintaining the stability of the battery capacity during long-term charge and discharge cycles, thereby extending the service life of the battery.
[0019] In a second aspect, an embodiment of the present application provides a method for preparing the positive electrode lithium supplement agent according to the first aspect, comprising the following steps:
[0020] Mixing the iron source, the lithium source, the source A and the source B to obtain a first mixed material;
[0021] Performing a first sintering process on the first mixed material to obtain a sintered material;
[0022] Mixing the sintered material, asphalt and grinding aid to obtain a second mixed material;
[0023] Dispersing, drying and performing a second sintering process on the second mixed material to obtain the positive electrode lithium supplement agent;
[0024] Wherein, the A source includes one or more of the oxide, fluoride, hydroxide and ethanolate of the A element; the B source includes one or more of the oxide, fluoride, hydroxide and ethanolate of the B element.
[0025] In the technical solution of the embodiment of the present application, the iron source, lithium source, source A and source B are mixed and then subjected to the first sintering to obtain a sintered material, which is a modified lithium-rich lithium iron oxide doped with elements A and B; then the sintered material, asphalt and a grinding aid are mixed and then dispersed, dried and subjected to the second sintering treatment to obtain a positive electrode lithium supplement with high conductivity, good air stability and high specific capacity. At the same time, an appropriate amount of grinding aid is introduced during the dispersion of the sintered material and asphalt, so that the recovery rate of the raw materials is high and the environmental pollution is small.
[0026] In some embodiments, the grinding aid includes one or more of N,N-dimethylformamide, tetrahydrofuran, toluene, cyclohexane, ethyl acetate, and acetone.
[0027] In this embodiment, grinding aids such as N,N-dimethylformamide, tetrahydrofuran, toluene, cyclohexane, ethyl acetate and acetone are relatively green and environmentally friendly organic solvents, which can not only improve the recovery rate of raw materials and be environmentally friendly, but also dissolve asphalt to a certain extent and improve the carbon coating effect, thereby enhancing the conductivity of the positive electrode lithium supplement.
[0028] In some embodiments, the mass ratio of modified lithium-rich lithium ferrite, asphalt and grinding aid is 100:(0.1~10):(20~40).
[0029] In this embodiment, the mass ratio of the modified lithium-rich lithium ferrate, asphalt and grinding aid is regulated, which is beneficial to forming a carbon coating layer with moderate thickness and high uniformity, and is beneficial to recycling raw materials and reducing environmental pollution.
[0030] In some embodiments, the temperature of the first sintering treatment is 500° C. to 900° C., and the time is 10 h to 40 h; the temperature of the second sintering treatment is 500° C. to 650° C., and the time is 1 h to 4 h.
[0031] In this embodiment, sintering at 500°C to 650°C for 1h to 4h can promote the decomposition of asphalt to form inorganic carbon material and coat the surface of the modified lithium iron-rich lithium ferrate, thereby improving the conductivity and air stability of the positive electrode lithium supplement.
[0032] In some embodiments, the iron source includes one or more of ferric phosphate, ferric oxide, ferric oxide, ferric hydroxide, and ferric oxyhydroxide.
[0033] In some embodiments, the iron source has a D50 particle size of 100 nm to 800 nm.
[0034] In this embodiment, the iron source is a nanoscale material with a small particle size, a large specific surface area and good dispersibility. It can be evenly distributed in the reaction system, which plays a role in accurately regulating the iron content and ensuring the accuracy of the chemical composition of the product. It can also improve the crystallinity and control the particle size, thereby improving the electrochemical performance of the positive electrode lithium supplement.
[0035] In some embodiments, the lithium source includes one or more of lithium oxide, lithium peroxide, lithium fluoride, lithium hydroxide, lithium carbonate, lithium nitrate, lithium acetate, and lithium oxalate.
[0036] In this embodiment, different lithium sources have different melting points and reaction activities. By rationally selecting or using them in combination, the reaction rate of the high-temperature solid-phase reaction can be regulated, the lithium content in the product can be accurately controlled, and the physical and electrochemical properties of the product can be optimized. At the same time, it is also beneficial to reduce the cost of raw materials and improve the economic benefits of the product.
[0037] In some embodiments, the molar ratio of the iron source, the lithium source, the A source, and the B source is 1:(4.95-5.25):(0-0.03):(0-0.03).
[0038] In this embodiment, the molar ratio of the iron source, lithium source, source A and source B is controlled within the above range. On the one hand, it can ensure the stoichiometric matching of each element, help optimize the crystal structure, and avoid the formation of impurities due to deficiency or excess of a certain element. On the other hand, it is beneficial to improve the diffusion efficiency of lithium ions and enhance the structural stability and cycle life of the material.
[0039] In a third aspect, an embodiment of the present application provides a positive electrode plate, which includes a positive electrode collector and a positive electrode active layer covering at least one surface of the positive electrode collector; the positive electrode active layer includes the positive electrode lithium replenisher described in the first aspect, or includes a positive electrode lithium replenisher prepared by the preparation method of the positive electrode lithium replenisher described in the second aspect.
[0040] In this embodiment, the positive electrode plate contains a positive electrode lithium supplement with high conductivity and good air stability, and thus has the advantages of higher specific capacity and lower internal resistance.
[0041] In some embodiments, the positive electrode active layer further includes a positive electrode active material, and the mass ratio of the positive electrode active material to the positive electrode lithium supplement is 100:(1-6).
[0042] In this embodiment, the mass ratio of the positive electrode active material to the positive electrode lithium supplement is 100:(1~6), which can provide an appropriate amount of lithium supplement to make up for the loss of active lithium without causing too little positive electrode active material, resulting in insufficient reversible lithium insertion vacancies in the positive electrode active layer and reducing the energy density of the battery.
[0043] In a fourth aspect, an embodiment of the present application provides a secondary battery, and the secondary battery includes the positive electrode plate described in the third aspect.
[0044] The secondary battery provided in the present application includes the above-mentioned positive electrode plate, and thus has the advantages of high positive electrode initial coulombic efficiency, long battery cycle life and low internal resistance.
[0045] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings used in the present application. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0047] Figure 1 A process flow chart of a method for preparing a positive electrode lithium supplement provided in an embodiment of the present application;
[0048] Figure 2 This is an X-ray diffraction (XRD) result diagram of the positive electrode lithium supplement agent obtained in Example 1 of the present application;
[0049] Figure 3 This is a comparison chart of the X-ray diffraction (XRD) results of the positive electrode lithium supplement agent obtained in Example 1 and Comparative Example 2 of the present application;
[0050] Figure 4 This is a comparison chart of the rate performance of the positive electrode lithium supplement obtained in Example 1 of the present application and Comparative Examples 2 to 4 at 2V to 4.5V. DETAILED DESCRIPTION
[0051] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0052] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0053] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0054] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0055] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0056] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).
[0057] the term
[0058] Unless otherwise specified or there is a contradiction, the terms and phrases used in this application have the following meanings:
[0059] Particle size: For spherical particles, particle size refers to the diameter of the spherical particles. For non-spherical particles, particle size usually refers to the equivalent particle size of the non-spherical particles (generally referred to as particle size). The particle size measured by a laser particle size analyzer is the equivalent diameter of the particle. Among them, the equivalent particle size means that when a certain physical property of a particle is the same or similar to that of a homogeneous spherical particle, the diameter of the spherical particle is used to represent the diameter of the actual particle. Unless otherwise specified or there is a contradiction, the particle size in this application represents the equivalent particle size.
[0060] Particle size distribution parameters: In the particle size distribution curve of particles, the particle size corresponding to the cumulative particle size distribution percentage reaching N% is called the DN particle size, which means that the particles smaller than this particle size account for N% of all particles, where N=0~100. When N=100, the D100 particle size indicates the particle size corresponding to the cumulative particle size distribution percentage reaching 100%. When N=50, the D50 particle size is the particle size corresponding to the cumulative particle size distribution percentage reaching 50%, indicating the median particle size or median diameter, indicating that particles smaller than and larger than this particle size each account for 50%. For example, D50 particle size = 1mm, which means that particles smaller than 1mm and particles larger than 1mm each account for 50% of all particles.
[0061] Crystallinity of carbon materials: Carbon materials have two characteristic peaks in Raman spectra: D peak and G peak. Among them, D peak is usually at 1350cm -1 It is related to the disordered structure and defects of carbon materials; the G peak is usually at 1580cm -1 The intensity ratio of D peak to G peak is denoted as I D / I G , which can characterize the crystallinity of carbon materials; I D / I GWhen the value of is low, it indicates that the crystallinity of the carbon material is high and the proportion of graphitized structure is higher; D / I G When the value is high, it indicates that the carbon material has low crystallinity and contains more disordered structures and defects.
[0062] Lithium iron-rich lithium oxide (Li5FeO4) has the advantages of high theoretical specific capacity and good structural stability. It can be used as a positive electrode lithium supplement to improve the first coulombic efficiency, energy density and cycle life of lithium-ion batteries. However, many problems arise in the process of using Li5FeO4 as a positive electrode lithium supplement. For example, Li5FeO4 has poor air stability and can react with water and CO2 in the air. In actual use, it will quickly denature and decompose in an environment with a relative humidity of 10%, and its lithium supplement effect cannot be exerted. This phenomenon will increase the residual alkali content on the surface during use, making the powder more hygroscopic, aggravating the side reactions caused by trace water impurities in the battery, and accelerating the aging of lithium-ion batteries. On the other hand, the alkaline surface of the material after decomposition is prone to cause cross-linking and breaking of the binder, causing poor chemical gelation of the positive electrode slurry, making the coating uniformity and consistency of the positive electrode active layer worse, and reducing the bonding force of the positive electrode active material on the surface of the current collector, which is easy to peel off, thereby affecting the battery performance. In addition, the poor conductivity of Li5FeO4 is not conducive to electron transmission, which limits the diffusion rate of lithium ions and leads to aggravated polarization and increased side reactions, thereby reducing the specific capacity of the material and the capacity retention rate after storage. Therefore, how to improve the air stability, conductivity and specific capacity of lithium iron-rich lithium ferrate materials is an urgent problem to be solved.
[0063] In order to solve the technical problems of extremely poor air stability, poor conductivity and low actual specific capacity of Li5FeO4 in traditional methods, the present application provides a positive electrode lithium supplement, a preparation method, a positive electrode plate and a secondary battery. The positive electrode lithium supplement provided by the present application has the advantages of high air stability, good conductivity and high specific capacity by co-doping multiple elements of lithium iron-rich lithium and loading a carbon coating layer on the surface of the inner core; further, the positive electrode lithium supplement is prepared by mixing, first sintering, dispersing, drying and second sintering treatment, which not only realizes multi-element co-doping and carbon coating modification treatment, so that the air stability, conductivity and specific capacity of the positive electrode lithium supplement are significantly improved, but also has the characteristics of simple process, high raw material recovery rate and low environmental pollution, so that the positive electrode plate and secondary battery using the positive electrode lithium supplement also have the advantages of high specific capacity, low internal resistance and long cycle life.
[0064] In the first aspect, the embodiment of the present application provides a positive electrode lithium supplement, which includes a core and a carbon coating layer covering the core; the core includes modified lithium-rich lithium ferrite, and its expression is: Li5Fe 1-x-y A xB y O4; wherein, 0 < x ≤ 0.03, 0 < y ≤ 0.03; the A element includes one or more of La, Sc, Y, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu; the B element includes one or more of Co, Ni, Cu, Zn, Mn, Cr, V, Ti, Zr, Nb, Mo, Ta, W, Sn, Sb, and Al; the mass ratio of the core to the carbon coating layer is 100: (0.1 - 6).
[0065] In the technical solution of the embodiment of the present application, the core of the cathode lithium supplementing agent uses modified lithium-rich iron oxide. By doping both the A element and the B element into the lithium-rich iron oxide, the conductivity of the cathode lithium supplementing agent is improved through the synergistic cooperation of multiple elements, making the migration and removal of lithium ions easier. Macroscopically, it is manifested as a significant reduction in the voltage plateau of the cathode lithium supplementing agent, thereby greatly increasing the specific capacity of the cathode lithium supplementing agent. At the same time, the carbon coating layer on the surface of the core can effectively isolate water and CO2 in the air and inhibit the occurrence of side reactions, thereby improving the air stability of the cathode lithium supplementing agent.
[0066] Among them, if the mass of the carbon coating layer is too low, it will affect the coating uniformity of the carbon coating layer and the protection effect on the core is not good; if the mass of the carbon coating layer is too high, it will cause a decline in the electrical performance of the cathode lithium supplementing agent. Controlling the mass ratio of the core to the carbon coating layer within the range of 100: (0.1 - 6) can not only ensure a good coating effect of the carbon coating layer on the surface of the core but also will not have an adverse impact on the electrical performance of the cathode lithium supplementing agent. Therefore, the cathode lithium supplementing agent provided by the present application has the advantages of high conductivity, good air stability, and high specific capacity, and can significantly improve the first Coulomb efficiency, energy density, and cycle life of secondary batteries such as lithium-ion batteries.
[0067] In this embodiment, the value of x includes but is not limited to 0.0001, 0.001, 0.002, 0.005, 0.008, 0.01, 0.012, 0.015, 0.018, 0.02, 0.022, 0.025, 0.028, or 0.03, etc., and the value of y includes but is not limited to 0.0001, 0.001, 0.002, 0.005, 0.008, 0.01, 0.012, 0.015, 0.018, 0.02, 0.022, 0.025, 0.028, or 0.03, etc.
[0068] In this embodiment, the mass ratio of the core to the carbon coating layer is 100:(0.1~6), including but not limited to 100:0.1, 100:0.2, 100:0.5, 100:0.8, 100:1, 100:1.5, 100:2, 100:2.5, 100:3, 100:3.5, 100:4, 100:4.5, 100:5, 100:5.5 or 100:6, etc.
[0069] In this embodiment, the A element is selected from at least one rare earth element, which can be any one of La, Sc, Y, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb and Lu, or a combination of at least two of the above rare earth elements, such as a combination of La and Sc, a combination of La and Y, a combination of La and Ce, a combination of La and Pr, a combination of La and Nd, a combination of La and Pm, a combination of La and Sm, a combination of La and Eu, a combination of La and Gd, a combination of La and Tb, a combination of La and Dy, a combination of La and Ho, a combination of La and Er, a combination of La and Tm, a combination of La and Yb, or a combination of La, Y and Ce, etc.
[0070] Furthermore, in some embodiments, the A element is La.
[0071] In this embodiment, the atomic radius of the La element is 188pm, which is much larger than the atomic radius of the Fe element (126pm). By doping with rare earth elements with larger atomic radius, the crystal structure of the material can be changed, the lattice spacing of the modified lithium-rich ferrite can be increased, and more transmission channels can be provided for lithium ions, making it easier for lithium ions to be embedded and removed, thereby improving the specific capacity and rate performance of the positive electrode lithium supplement. In addition, the doping of the La element can also enhance the structural stability of the core, reduce the capacity loss and performance attenuation in long-term charge and discharge cycles, and thus improve the cycle stability of the positive electrode lithium supplement.
[0072] In this embodiment, the B element is selected from at least one transition metal element, which can be any one of Co, Ni, Cu, Zn, Mn, Cr, V, Ti, Zr, Nb, Mo, Ta, W, Sn, Sb and Al, or a combination of at least two of Co, Ni, Cu, Zn, Mn, Cr, V, Ti, Zr, Nb, Mo, Ta, W, Sn, Sb and Al, such as a combination of Co and Ni, a combination of Co and Cu, a combination of Co and Zn, a combination of Co and Mn, a combination of Co and Cr, a combination of Co and V, a combination of Co and Ti, a combination of Co and Zr, a combination of Co and Nb, a combination of Co and Mo, a combination of Co and Ta, a combination of Co and W, a combination of Co and Sn, a combination of Co and Sb, a combination of Co and Al, or a combination of Co, Ni and Mn, etc.
[0073] Furthermore, in some embodiments, the B element is Co.
[0074] In this embodiment, the doping of Co element can stabilize the local environment of Fe element in the core, promote the formation of π-symmetric bonding orbitals, and macroscopically manifest as lower overpotential and relatively low starting voltage. In addition, the doping of Co element can also improve the electronic conductivity of the modified lithium-rich lithium ferrite, promote the diffusion of lithium ions, and thus improve the specific capacity and rate performance of the positive electrode lithium supplement.
[0075] Further, in some embodiments, the thickness of the carbon coating layer is 0.1nm~500nm, including but not limited to 0.1nm, 0.5nm, 1nm, 5nm, 10nm, 20nm, 50nm, 80nm, 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm or 500nm, etc.
[0076] In this embodiment, the thickness of the carbon coating layer is controlled between 0.1nm and 500nm, which can be relatively evenly covered on the surface of the core, forming a good conductive network, promoting electron transfer, and improving the rate performance of the material. If the thickness of the carbon coating layer is too small, a conductive network cannot be formed, and the conductivity of the material cannot be improved; if the thickness of the carbon coating layer is too large, the overall weight of the material will increase, and the specific capacity will be reduced.
[0077] Further, in some embodiments, the D50 particle size of the inner core is 1 μm to 6 μm, including but not limited to 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm or 6 μm, etc.
[0078] In this embodiment, the D50 particle size of the core of the positive electrode lithium supplement agent is moderate, which can ensure that the diffusion path of lithium ions inside the material is not too long or too short, and lithium ions can be embedded and extracted relatively quickly, thereby improving the specific capacity and rate performance of the battery. At the same time, within this particle size range, the positive electrode lithium supplement agent is easy to disperse in the electrode slurry, which is conducive to forming a positive electrode active coating with high flatness and good uniformity, thereby improving the consistency and stability of the positive electrode.
[0079] Further, in some embodiments, the 0.05C discharge specific capacity of the positive electrode lithium supplement is ≥680mAh / g, including but not limited to 680mAh / g, 690mAh / g, 700mAh / g, 710mAh / g, 720mAh / g, 730mAh / g, 740mAh / g, 750mAh / g, 760mAh / g, 770mAh / g or 780mAh / g, etc.
[0080] In this embodiment, the positive electrode lithium supplement has a high specific capacity and can provide a large amount of additional lithium source for the battery, thereby increasing the overall capacity of the battery and improving the rate performance, and maintaining the stability of the battery capacity during long-term charge and discharge cycles, thereby extending the service life of the battery.
[0081] See also Figure 1 In a second aspect, an embodiment of the present application provides a method for preparing a positive electrode lithium replenisher, which is used to prepare the positive electrode lithium replenisher described in the first aspect.
[0082] like Figure 1 As shown, the preparation method of the positive electrode lithium supplement comprises the following steps:
[0083] S1, mixing the iron source, the lithium source, the source A and the source B to obtain a first mixed material;
[0084] S2, performing a first sintering process on the first mixed material to obtain a sintered material;
[0085] S3, mixing the sintered material, asphalt and grinding aid to obtain a second mixed material;
[0086] S4, dispersing, drying and second sintering the second mixed material to obtain a positive electrode lithium supplement;
[0087] Wherein, the A source includes one or more of the oxide, fluoride, hydroxide and ethanolate of the A element; the B source includes one or more of the oxide, fluoride, hydroxide and ethanolate of the B element.
[0088] In the technical solution of the embodiment of the present application, the iron source, lithium source, source A and source B are mixed and then subjected to the first sintering to obtain a sintered material, which is a modified lithium-rich lithium iron oxide doped with elements A and B; then the sintered material, asphalt and a grinding aid are mixed and then dispersed, dried and subjected to the second sintering treatment to obtain a positive electrode lithium supplement with high conductivity, good air stability and high specific capacity. At the same time, an appropriate amount of grinding aid is introduced during the dispersion of the sintered material and asphalt, so that the recovery rate of the raw materials is high and the environmental pollution is small.
[0089] The following is a detailed description of the preparation method of the positive electrode lithium supplement agent in a step-by-step manner.
[0090] S1. Mixing an iron source, a lithium source, a source A and a source B to obtain a first mixed material.
[0091] Further, in some embodiments, the iron source includes one or more of ferric phosphate, ferric oxide, ferric tetroxide, ferric hydroxide and ferric oxyhydroxide. It is understandable that the iron source can be any one of ferric phosphate, ferric oxide, ferric tetroxide, ferric hydroxide and ferric oxyhydroxide, or a combination of at least two of ferric phosphate, ferric oxide, ferric tetroxide, ferric hydroxide and ferric oxyhydroxide, such as a combination of ferric phosphate and ferric oxide, a combination of ferric oxide and ferric oxide, a combination of ferric hydroxide and ferric oxide, a combination of ferric oxide and ferric oxide, or a combination of ferric oxide, ferric oxide and ferric hydroxide. Further, in some embodiments, the iron source is ferric oxide, also known as iron oxide or iron red, with a chemical formula of Fe2O3.
[0092] Further, in some embodiments, the D50 particle size of the iron source is 100 nm to 800 nm, including but not limited to 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm or 800 nm.
[0093] In this embodiment, the iron source is a nanoscale material with a small particle size, a large specific surface area and good dispersibility. It can be evenly distributed in the reaction system, which plays a role in accurately regulating the iron content and ensuring the accuracy of the chemical composition of the product. It can also improve the crystallinity and control the particle size, thereby improving the electrochemical performance of the positive electrode lithium supplement.
[0094] Further, in some embodiments, the lithium source includes one or more of lithium oxide, lithium peroxide, lithium fluoride, lithium hydroxide, lithium carbonate, lithium nitrate, lithium acetate and lithium oxalate. It is understandable that the lithium source can be any one of lithium oxide, lithium peroxide, lithium fluoride, lithium hydroxide, lithium carbonate, lithium nitrate, lithium acetate and lithium oxalate, or a combination of at least two of lithium oxide, lithium peroxide, lithium fluoride, lithium hydroxide, lithium carbonate, lithium nitrate, lithium acetate and lithium oxalate, such as a combination of lithium oxide and lithium peroxide, a combination of lithium oxide and lithium fluoride, a combination of lithium oxide and lithium hydroxide, a combination of lithium oxide and lithium carbonate, a combination of lithium oxide and lithium nitrate, a combination of lithium oxide and lithium acetate, a combination of lithium oxide and lithium oxalate, or a combination of lithium oxide, lithium hydroxide and lithium carbonate, etc.
[0095] In this embodiment, different lithium sources have different melting points and reaction activities. By rationally selecting or using them in combination, the reaction rate of the high-temperature solid-phase reaction can be regulated, the lithium content in the product can be accurately controlled, and the physical and electrochemical properties of the product can be optimized. At the same time, it is also beneficial to reduce the cost of raw materials and improve the economic benefits of the product.
[0096] Furthermore, in some embodiments, the lithium source includes lithium oxide and lithium hydroxide, and the molar ratio of lithium oxide to lithium hydroxide is 1:(1.5~2.5), including but not limited to 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9, 1:2, 1:2.1, 1:2.2, 1:2.3, 1:2.4 or 1:2.5, etc. Preferably, the molar ratio of lithium oxide to lithium hydroxide is 1:2.
[0097] In this embodiment, the melting point of lithium oxide is relatively high, and the melting point of lithium hydroxide is relatively low. By matching lithium sources with different melting points, the sintering reaction time can be shortened and the corrosion of the lithium source on the equipment can be reduced. At the same time, the price of lithium hydroxide is relatively low, and the molar ratio of lithium oxide to lithium hydroxide is controlled at 1: (1.5~2.5), which is conducive to controlling the preparation cost of the positive electrode lithium supplement.
[0098] Further, in some embodiments, the A source includes one or more of the oxide, fluoride, hydroxide and ethanolate of the element A, and can be further selected as the oxide of the element A, such as lanthanum oxide, scandium oxide, yttrium oxide, cerium oxide or dysprosium oxide.
[0099] Further, in some embodiments, the B source includes one or more of the oxides, fluorides, hydroxides and ethanolates of the B element, and can be further selected as oxides of the B element, such as cobalt oxide, nickel oxide, copper oxide, zinc oxide, manganese oxide, chromium oxide, vanadium oxide, titanium oxide, zirconium oxide, niobium oxide, molybdenum oxide, tantalum oxide, tungsten oxide, tin oxide, antimony oxide or aluminum oxide, etc.
[0100] Further, in some embodiments, the molar ratio of the iron source, the lithium source, the source A and the source B is 1:(4.95-5.25):(0-0.03):(0-0.03). It is understandable that in this molar ratio, the amount of the source A and the source B is not zero.
[0101] In this embodiment, the molar ratio of the iron source to the lithium source includes but is not limited to 1:4.95, 1:5.00, 1:5.05, 1:5.10, 1:5.15, 1:5.20 or 1:5.25, etc.; the molar ratio of the iron source to the A source includes but is not limited to 1:0.0001, 1:0.001, 1:0.002, 1:0.005, 1:0.008, 1:0.01, 1:0.012, 1:0.015, 1:0.018, 1:0 .02, 1:0.022, 1:0.025, 1:0.028 or 1:0.03, etc.; the molar ratio of the iron source to the B source includes but is not limited to 1:0.0001, 1:0.001, 1:0.002, 1:0.005, 1:0.008, 1:0.01, 1:0.012, 1:0.015, 1:0.018, 1:0.02, 1:0.022, 1:0.025, 1:0.028 or 1:0.03, etc.
[0102] In this embodiment, the molar ratio of the iron source, lithium source, source A and source B is controlled within the above range. On the one hand, it can ensure the stoichiometric matching of each element, help optimize the crystal structure, and avoid the formation of impurities due to deficiency or excess of a certain element. On the other hand, it is beneficial to improve the diffusion efficiency of lithium ions and enhance the structural stability and cycle life of the material.
[0103] S2. Performing a first sintering process on the first mixed material to obtain a sintered material.
[0104] Further, in some embodiments, the temperature of the first sintering treatment is 500°C~900°C, including but not limited to 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C or 900°C, etc.; the time of the first sintering treatment is 10h~40h, including but not limited to 10h, 12h, 15h, 18h, 20h, 22h, 25h, 28h, 30h, 32h, 35h, 38h or 40h.
[0105] Furthermore, in some embodiments, after the first sintering process, the following steps are also included: a sintered material with a D50 particle size of 1 μm to 3 μm is obtained by crushing and ball milling.
[0106] S3, mixing the sintered material, asphalt and grinding aid to obtain a second mixed material.
[0107] Further, in some embodiments, the grinding aid includes one or more of N,N-dimethylformamide (DMF), tetrahydrofuran (THF), toluene, cyclohexane, ethyl acetate and acetone.
[0108] In this embodiment, the grinding aid can be selected from any one of N,N-dimethylformamide, tetrahydrofuran, toluene, cyclohexane, ethyl acetate and acetone, or a combination of at least two of N,N-dimethylformamide, tetrahydrofuran, toluene, cyclohexane, ethyl acetate and acetone. These grinding aids are relatively green and environmentally friendly organic solvents, which can not only improve the recovery rate of raw materials and be environmentally friendly, but also dissolve asphalt to a certain extent, improve the carbon coating effect, and thus improve the conductivity of the positive electrode lithium supplement.
[0109] Furthermore, in some embodiments, the mass ratio of the modified lithium-rich lithium ferrite, asphalt and grinding aid is 100:(0.1~10):(20~40).
[0110] In this embodiment, the mass ratio of the modified lithium-rich lithium iron oxide, asphalt and grinding aid is regulated, which is conducive to forming a carbon coating layer with moderate thickness and high uniformity, and is conducive to recycling raw materials and reducing environmental pollution. Among them, the mass ratio of the modified lithium-rich lithium iron oxide and asphalt can be 100:0.1, 100:0.2, 100:0.5, 100:0.8, 100:1, 100:2, 100:3, 100:4, 100:5, 100:6, 100:7, 100:8, 100:9 or 100:10, etc. The mass ratio of the modified lithium-rich lithium ferrate and the grinding aid is 100:20, 100:22, 100:24, 100:26, 100:28, 100:30, 100:32, 100:34, 100:36, 100:38 or 100:40, etc.
[0111] S4, dispersing, drying and performing a second sintering treatment on the second mixed material to obtain a positive electrode lithium supplement.
[0112] Further, in some embodiments, the step of dispersing the second mixed material comprises: crushing and ball milling the second mixed material. The ball milling is performed under vacuum; the ball milling speed is 300 rpm to 500 rpm, including but not limited to 300 rpm, 350 rpm, 400 rpm, 450 rpm or 500 rpm; the ball milling time is 1 h to 8 h, including but not limited to 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h or 8 h; the ball to material ratio is (1 to 10): 1, including but not limited to 1: 1, 2: 1, 3: 1, 4: 1, 5: 1, 6: 1, 7: 1, 8: 1, 9: 1 or 10: 1.
[0113] In this embodiment, the particles of the second mixed material can be refined through crushing and ball milling, and the components can be fully contacted and evenly dispersed, which is beneficial to improving the reaction rate of the second sintering process.
[0114] Furthermore, in some embodiments, the drying treatment temperature is 60°C~100°C, including but not limited to 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C or 100°C, etc.; the drying treatment time is 1h~5h, including but not limited to 1h, 2h, 3h, 4h or 5h, etc.
[0115] Further, in some embodiments, the temperature of the second sintering treatment is 500℃~650℃, including but not limited to 500℃, 520℃, 540℃, 550℃, 560℃, 580℃, 600℃, 620℃, 630℃, 640℃ or 650℃, etc.; the time of the second sintering treatment is 1h~4h, including but not limited to 1h, 1.5h, 2h, 2.5h, 3h, 3.5h or 4h.
[0116] In this embodiment, sintering at 500°C to 650°C for 1h to 4h can promote the decomposition of asphalt to form inorganic carbon material and coat the surface of the modified lithium-rich lithium ferrite, thereby improving the intrinsic conductivity and air stability of the positive electrode lithium supplement.
[0117] In a third aspect, an embodiment of the present application provides a positive electrode plate, which includes a positive electrode collector and a positive electrode active layer covering at least one surface of the positive electrode collector; the positive electrode active layer includes the positive electrode lithium replenisher described in the first aspect, or includes a positive electrode lithium replenisher prepared by the preparation method of the positive electrode lithium replenisher described in the second aspect.
[0118] In this embodiment, the positive electrode active layer on the positive electrode plate contains a positive electrode lithium supplement with high conductivity, good air stability and high specific capacity, and thus has the advantages of higher specific capacity and lower internal resistance.
[0119] Furthermore, in some embodiments, the positive electrode active layer also includes a positive electrode active material, and the mass ratio of the positive electrode active material to the positive electrode lithium supplement is 100:(1~6), including but not limited to 100:1, 100:2, 100:3, 100:4, 100:5 or 100:6.
[0120] In this embodiment, the mass ratio of the positive electrode active material to the positive electrode lithium supplement is 100:(1~6), which can provide an appropriate amount of lithium supplement to make up for the loss of active lithium without causing too little positive electrode active material, resulting in insufficient reversible lithium insertion vacancies in the positive electrode active layer and reducing the energy density of the battery.
[0121] Furthermore, in some embodiments, the positive electrode current collector includes a metal current collector or a composite current collector. The metal current collector may be aluminum foil; the composite current collector includes a polymer substrate and a metal layer formed on the polymer substrate, the polymer substrate may be made of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE), and the metal layer may be made of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy.
[0122] Further, in some embodiments, the positive electrode active material includes one or more of a lithium transition metal oxide and an olivine structured lithium phosphate. Among them, the lithium transition metal oxide includes but is not limited to: lithium cobalt oxide, such as LiCoO2; lithium nickel oxide, such as LiNiO2; lithium manganese oxide, such as LiMnO2 or LiMn2O4; lithium nickel cobalt oxide; lithium manganese cobalt oxide; lithium nickel manganese oxide; lithium nickel cobalt manganese oxide, such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O2 (NCM523), LiNi 0.5 Co 0.25 Mn 0.25 O2 (NCM211), LiNi 0.6 Co 0.2 Mn 0.2 O2 (NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811); lithium nickel cobalt aluminum oxide, such as LiNi 0.8 Co 0.15 Al 0.05 O2; and modified compounds of the above lithium transition metal oxides. Lithium phosphates with an olivine structure include but are not limited to: lithium iron phosphate, such as LiFePO4 (LFP); a composite material of lithium iron phosphate and carbon; lithium manganese phosphate, such as LiMnPO4; a composite material of lithium manganese phosphate and carbon; lithium iron manganese phosphate; a composite material of lithium iron manganese phosphate and carbon; and modified compounds of the above lithium phosphates with an olivine structure. The modified compounds of each material can be one or more of doping modification and surface coating modification.
[0123] Furthermore, in some embodiments, the positive electrode active layer further includes a binder and a conductive agent. The binder includes one or more of polyvinylidene fluoride (PVDF), sodium alginate (SA), polyvinyl alcohol (PVA), polymethyl methacrylate (PMMA), hydrogenated nitrile rubber (HNBR), polytetrafluoroethylene (PTFE) and polyacrylic acid (PAA). The conductive agent includes one or more of conductive carbon, superconducting carbon, acetylene black, carbon black, Ketjen black, carbon quantum dots, carbon nanotubes, graphene and carbon nanofibers.
[0124] In a fourth aspect, an embodiment of the present application provides a secondary battery, which includes the positive electrode plate described in the third aspect.
[0125] The secondary battery provided in the present application includes the above-mentioned positive electrode plate, and thus has the advantages of high positive electrode initial coulombic efficiency, long battery cycle life and low internal resistance.
[0126] Some specific embodiments are listed below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be obtained commercially.
[0127] Example 1
[0128] Please refer to Table 1, the preparation method of the positive electrode lithium supplement in this embodiment is as follows:
[0129] (1) Weighing an iron source, a lithium source, a source A and a source B, and mixing them evenly with an oblique mixer to obtain a first mixed material; then subjecting the first mixed material to a first sintering treatment at 600° C. for 40 h, and after crushing and ball milling, obtaining a sintered material with a D50 particle size of 2 μm, wherein the sintered material is modified lithium-rich lithium ferrate.
[0130] Among them, the iron source is 0.05mol nano-iron oxide, and the D50 particle size is 500nm;
[0131] The lithium source is 0.125 mol of lithium oxide and 0.25 mol of lithium hydroxide;
[0132] Source A is 0.00009 mol (900 ppm) of lanthanum trioxide (La2O3);
[0133] The B source is 0.00012 mol (1200 ppm) of cobalt trioxide (Co2O3).
[0134] (2) Weighing the sintered material, asphalt and grinding aid obtained in step (1), mixing them to obtain a second mixed material; crushing the second mixed material and subjecting it to vacuum ball milling at a ball milling speed of 500 rpm, a ball milling time of 4 h, and a ball-to-material ratio of 5:1; after the ball milling, vacuum drying at 80° C. for 2 h, and subjecting it to a second sintering treatment at 600° C. for 4 h to form a carbon coating layer on the surface of the modified lithium-rich lithium ferrate, thereby preparing a positive electrode lithium supplement.
[0135] Wherein, the grinding aid is N,N-dimethylformamide (DMF);
[0136] The mass ratio of modified lithium-rich lithium ferrate, asphalt and grinding aid is 100:4:30.
[0137] Embodiment 2~4
[0138] The difference between Examples 2 to 4 and Example 1 is that the amount of asphalt used is different, as follows:
[0139] Example 2: The mass ratio of modified lithium-rich lithium ferrate, asphalt and grinding aid is 100:3:30.
[0140] Example 3: The mass ratio of modified lithium-rich lithium ferrate, asphalt and grinding aid is 100:5:30.
[0141] Example 4: The mass ratio of modified lithium-rich lithium ferrate, asphalt and grinding aid is 100:6:30.
[0142] Embodiment 5~9
[0143] The difference between Examples 5 to 9 and Example 1 is that the types of grinding aids are different, as follows:
[0144] Example 5: N,N-dimethylformamide was replaced with an equal mass of tetrahydrofuran (THF).
[0145] Example 6: N,N-dimethylformamide is replaced by an equal mass of toluene (MT).
[0146] Example 7: N,N-dimethylformamide is replaced by an equal mass of cyclohexane (CYH).
[0147] Example 8: N,N-dimethylformamide was replaced with an equal mass of ethyl acetate (EAC).
[0148] Example 9: N,N-dimethylformamide is replaced by an equal mass of acetone (ACE).
[0149] Embodiments 10 to 15
[0150] The difference between Examples 10 to 15 and Example 1 is that the conditions of the second sintering treatment in step (2) are different, as follows:
[0151] Example 10: The second sintering temperature is reduced from 600°C to 500°C.
[0152] Example 11: The second sintering temperature is reduced from 600°C to 550°C.
[0153] Example 12: The second sintering temperature is increased from 600°C to 650°C.
[0154] Example 13: The second sintering time is shortened from 4 h to 3 h.
[0155] Example 14: The second sintering time is shortened from 4 h to 2 h.
[0156] Example 15: The second sintering time is shortened from 4 h to 1 h.
[0157] Embodiments 16 to 18
[0158] The difference between Examples 16 to 18 and Example 1 is that the amount of La2O3 and / or Co2O3 used in step (1) is different, as follows:
[0159] Example 16: Source A is selected from 300 ppm of La2O3, and source B is selected from 600 ppm of Co2O3.
[0160] Example 17: Source A is selected from 600 ppm La2O3, and source B is selected from 900 ppm Co2O3.
[0161] Example 18: Source A is selected from 1200 ppm La2O3, and source B is selected from 1200 ppm Co2O3.
[0162] Embodiment 19-20
[0163] The difference between this embodiment and embodiment 1 is that the source A or source B in step (1) is different, as follows:
[0164] Example 19: Source A uses 900 ppm CeO2 and source B uses 1200 ppm Co2O3.
[0165] Example 20: Source A is selected from 900 ppm La2O3, and source B is selected from 1200 ppm Al2O3.
[0166] Comparative Examples 1 to 7
[0167] Comparative Examples 1 to 7 are substantially the same as Example 1, except that:
[0168] Comparative Example 1: La2O3 and Co2O3 are not added in step (1), and step (2) is not performed, that is, the positive electrode lithium supplement is undoped and uncarbon-coated lithium iron-rich lithium.
[0169] Comparative Example 2: La2O3 and Co2O3 are not added in step (1).
[0170] Comparative Example 3: La2O3 is not added in step (1).
[0171] Comparative Example 4: No Co2O3 was added in step (1).
[0172] Comparative Example 5: The carbon coating treatment in step (2) was not performed.
[0173] Comparative Example 6: The asphalt in step (2) is replaced by an equal mass of glucose.
[0174] Comparative Example 7: No grinding aid was added during the ball milling process in step (2).
[0175] Test Case
[0176] 1. Test items:
[0177] 1. XRD test: The phase analysis of the positive electrode lithium supplement obtained in Example 1 and Comparative Examples 2 to 4 was performed using a Bruker D8 Advance X-ray diffractometer produced by Bruker, Germany. The results are shown in Figure 2~3 .
[0178] 2. Particle size test: The particle size analysis was performed using the Mastersizer 2000 laser particle size analyzer produced by Malvern Instruments Ltd., UK. The results are shown in Table 2.
[0179] 3. Raman test: Raman spectrometer in Via produced by Renishaw of the United Kingdom was used to perform Raman spectroscopy analysis on the positive electrode lithium supplements obtained in Example 1, Examples 5 to 9 and Comparative Examples 5 to 7. The results are shown in Table 2.
[0180] 4. TEM test: A transmission electron microscope (TEM) of the FEI Tecnai G2 F20 X-Twin model produced by Thermo Fisher Scientific Inc. of the United States was used to analyze the morphology of the positive electrode lithium supplement obtained in each embodiment and each comparative example, and the thickness of the carbon coating layer was measured. The results are shown in Table 2.
[0181] 5. Performance test of secondary batteries
[0182] The positive electrode active material NCM811 was mixed with the conductive carbon black, the binder PVDF and the positive electrode lithium supplement obtained in each embodiment and each comparative example in a mass ratio of 90.8:4:3:2.2 to obtain a positive electrode slurry; the positive electrode slurry was coated on an aluminum foil with a thickness of 12 μm to form a positive electrode slurry layer with a thickness of 80 μm; then it was placed in an oven at 110°C and dried for 10 hours, and after drying, it was punched into a circular electrode piece with a diameter of 15 mm, and pressed to a compact density of 1.8 g / cm 3 Roll-pressing is performed to obtain a positive electrode sheet.
[0183] Lithium hexafluorophosphate (LiPF6) was used as lithium salt, and ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) with a volume ratio of 1:1:1 were used as organic solvents. The lithium salt was dissolved in the organic solvent to prepare an electrolyte with a concentration of 1M. A lithium sheet with a diameter of 16 mm was used as the counter electrode, and the battery was assembled with the positive electrode sheet and the electrolyte in the LG2400 / 1000TS glove box produced by Weige Gas Purification Technology (Suzhou) Co., Ltd. to obtain a button half-cell.
[0184] The button half-cell was tested for capacity and cycle using the CT3002A battery performance test system produced by Wuhan Blue Electric Electronic Technology Co., Ltd. The test temperature was 25°C, the voltage range was 2~4.5V, and the rate range was 0.1C~3C. The results are shown in Table 2 and Figure 4 .
[0185] The internal resistance test of the button half-cell was conducted using an internal resistance tester of model ST2742B produced by Suzhou Jingge Electronics Co., Ltd. The results are shown in Table 2.
[0186] 2. Results Analysis
[0187] Table 1. Relevant parameters of the preparation process of positive electrode lithium supplement
[0188]
[0189] Table 2. Performance of positive electrode lithium supplement
[0190]
[0191] Depend on Figure 2 It can be seen that the XRD spectrum of the positive electrode lithium supplement obtained in Example 1 has no impurity peaks, and Figure 3 It can be seen that compared with the positive electrode lithium replenisher of comparative example 2, the diffraction peak of the positive electrode lithium replenisher of embodiment 1 shifts to the left, that is, the lattice spacing of the positive electrode lithium replenisher doped with La element increases, making it easier for lithium ions to embed and escape, which is manifested in that the specific capacity of the positive electrode lithium replenisher is greatly increased on a macro scale.
[0192] As shown in Table 2, the positive electrode lithium supplements obtained in Examples 1 to 20 have a core D50 particle size between 1.94 μm and 5.57 μm, a carbon coating layer thickness between 39.84 nm and 44.99 nm, and a ratio of the intensity of the D peak to the intensity of the G peak (I D / I G ) is between 0.9305 and 0.9886, the voltage platform after being assembled into a button-type half-cell is below 4.35V, the 0.05C discharge specific capacity is between 684mAh / g and 764mAh / g, and the internal resistance is between 18.42mΩ and 20.89mΩ, indicating that the positive electrode lithium supplement obtained in Examples 1 to 20 has a high discharge specific capacity and good electronic conductivity.
[0193] Depend on Figure 4 It can be seen that compared with Example 1, the positive electrode lithium supplement agent obtained in Comparative Examples 1 to 5 has a significantly lower discharge capacity and a significantly increased internal resistance, which proves that the positive electrode lithium supplement agent in Example 1 can achieve better electronic conductivity and higher discharge capacity under the cooperation of lanthanum and cobalt co-doping and carbon coating. D / I G The carbon layer crystallinity increased, but the 0.05C discharge capacity decreased to 700 mAh / g, and the internal resistance increased to 25.89 mΩ, indicating that when asphalt is used as the carbon source, the obtained carbon coating layer has a better coating effect and better electronic conductivity, which is manifested in that the internal resistance of the positive electrode lithium supplement is greatly reduced and the discharge capacity is greatly increased. In comparative example 7, no grinding aid is added during the ball milling process, resulting in a very poor carbon coating effect, so the electronic conductivity and discharge capacity of the positive electrode lithium supplement are further reduced.
[0194] The difference between Examples 2 to 4 and Example 1 is only the amount of asphalt used. The D50 particle size of the core of the obtained positive electrode lithium supplement is ≤2.16 μm, the thickness of the carbon coating layer is ≤40.49 nm, and the I D / I G ≤0.9483, while the 0.05C discharge specific capacity of the button half-cell is ≥750mAh / g, the internal resistance is ≤18.95mΩ, and when the mass ratio of the modified lithium-rich lithium ferrite, asphalt and grinding aid in Example 1 is 100:4:30, the positive electrode lithium supplement has better electronic conductivity and higher discharge specific capacity.
[0195] The only difference between Examples 5 to 9 and Example 1 is the different types of grinding aids, which significantly increase the D50 particle size of the core of the positive electrode lithium supplement and the thickness of the carbon coating layer, and reduce the 0.05C discharge specific capacity and increase the internal resistance, proving that compared with grinding aids such as tetrahydrofuran and toluene, N,N-dimethylformamide has a better grinding aid effect.
[0196] The only difference between Examples 10 to 15 and Example 1 is that the conditions of the second sintering treatment are different, which significantly increases the D50 particle size of the core of the positive electrode lithium replenisher and the thickness of the carbon coating layer, and reduces the 0.05C discharge specific capacity and increases the internal resistance, proving that the sintering effect is best when the temperature of the second sintering treatment is 600°C and the time is 4h, and the obtained positive electrode lithium replenisher exhibits better electronic conductivity and higher discharge specific capacity.
[0197] The difference between Examples 16 to 18 and Example 1 is that the amount of La2O3 and / or Co2O3 used is different, which significantly increases the D50 particle size of the core of the positive electrode lithium supplement and the thickness of the carbon coating layer, slightly decreases the 0.05C discharge specific capacity, and significantly increases the internal resistance, proving that when the amount of La2O3 is 900ppm and the amount of Co2O3 is 1200ppm, the mixed doping effect of lanthanum and cobalt is best.
[0198] In Example 19, source A was replaced by La2O3 with CeO2, and in Example 20, source B was replaced by Al2O3. The D50 particle size of the obtained positive electrode lithium supplement was greatly improved, the thickness of the carbon coating layer was increased, the 0.05C discharge specific capacity was greatly reduced, and the internal resistance was significantly increased, which proved that compared with the combination of cerium and cobalt and the combination of lanthanum and aluminum, the mixed doping of lanthanum and cobalt can exert a better synergistic effect, thereby greatly improving the electronic conductivity and discharge specific capacity of the material.
[0199] In summary, the core of the positive electrode lithium supplement provided in the present application adopts modified lithium-rich lithium iron oxide. By simultaneously doping element A and element B in the lithium-rich lithium iron oxide, the conductivity of the positive electrode lithium supplement is improved by utilizing the synergistic cooperation of multiple elements, making it easier for lithium ions to migrate and escape, thereby greatly increasing the specific capacity of the material.
[0200] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A positive electrode lithium supplement, characterized in that: comprising a core and a carbon coating layer covering the core; The core includes modified lithium-rich lithium iron oxide, which is expressed as: Li5Fe 1-x-y A x B y O4; Among them, 0 <x≤0.03,0<y≤0.03; The A element includes one or more of La, Sc, Y, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb and Lu; The B element includes one or more of Co, Ni, Cu, Zn, Mn, Cr, V, Ti, Zr, Nb, Mo, Ta, W, Sn, Sb and Al; The mass ratio of the core to the carbon coating layer is 100:(0.1-6).
2. The positive electrode lithium supplement according to claim 1, characterized in that: The positive electrode lithium supplement meets one or more of the following conditions: (1) The thickness of the carbon coating layer is 0.1 nm to 500 nm; (2) The D50 particle size of the core is 1 μm to 6 μm; (3) The 0.05C discharge specific capacity of the positive electrode lithium supplement is ≥ 680 mAh / g.
3. A method for preparing a positive electrode lithium supplement according to claim 1 or 2, characterized in that: The following steps are involved: Mixing the iron source, the lithium source, the source A and the source B to obtain a first mixed material; Performing a first sintering process on the first mixed material to obtain a sintered material; Mixing the sintered material, asphalt and grinding aid to obtain a second mixed material; Dispersing, drying and performing a second sintering process on the second mixed material to obtain the positive electrode lithium supplement agent; Wherein, the A source includes one or more of the oxide, fluoride, hydroxide and ethanolate of the A element; the B source includes one or more of the oxide, fluoride, hydroxide and ethanolate of the B element.
4. The method for preparing a positive electrode lithium supplement according to claim 3, characterized in that: The grinding aid includes one or more of N,N-dimethylformamide, tetrahydrofuran, toluene, cyclohexane, ethyl acetate and acetone.
5. The method for preparing a positive electrode lithium supplement according to claim 4, characterized in that: The mass ratio of the sintered material, the asphalt and the grinding aid is 100:(0.1-10):(20-40).
6. The method for preparing a positive electrode lithium supplement according to claim 3, characterized in that: The temperature of the first sintering treatment is 500° C. to 900° C., and the time is 10 h to 40 h; the temperature of the second sintering treatment is 500° C. to 650° C., and the time is 1 h to 4 h.
7. The method for preparing a positive electrode lithium supplement according to any one of claim 3, characterized in that: One or more of the following conditions are met: (1) The iron source includes one or more of ferric phosphate, ferric oxide, ferric oxide, ferric hydroxide and ferric oxyhydroxide; (2) The D50 particle size of the iron source is 100 nm to 800 nm; (3) The lithium source includes one or more of lithium oxide, lithium peroxide, lithium fluoride, lithium hydroxide, lithium carbonate, lithium nitrate, lithium acetate and lithium oxalate; (4) The molar ratio of the iron source, the lithium source, the source A and the source B is 1:(4.95-5.25):(0-0.03):(0-0.03).
8. A positive electrode sheet, characterized in that: It includes a positive electrode current collector and a positive electrode active layer covering at least one surface of the positive electrode current collector; The positive electrode active layer comprises the positive electrode lithium replenisher according to claim 1 or 2, or comprises the positive electrode lithium replenisher prepared by the preparation method of the positive electrode lithium replenisher according to any one of claims 3 to 7.
9. The positive electrode sheet according to claim 8, characterized in that: The positive electrode active layer further includes a positive electrode active material, and the mass ratio of the positive electrode active material to the positive electrode lithium supplement is 100:(1-6).
10. A secondary battery, characterized in that: The secondary battery comprises the positive electrode sheet according to claim 8 or 9.
Citation Information
Patent Citations
Modified positive electrode lithium supplement additive and preparation method and application thereof
CN115832471A
Lithium-rich lithium ferrite lithium supplement material and preparation method thereof
CN117558922A
Lithium-rich lithium ferrite material as well as preparation method and application thereof
CN118198536A
Positive lithium supplement agent, preparation method thereof, positive plate and lithium ion battery
CN118431478A
Lithium-rich lithium ferrite material as well as preparation method and application thereof
CN118970048A
Cited By
Battery and electric device comprising same
CN121355220A